Morgan, Julia, studio portrait - Boyé Studio, San Francisco::::::photographer::: (1926)
The date of 1926 is based on Sara Holmes Boutelle's date in her 1988 biography of Julia Morgan "Julia Morgan: Architect" but the year may be disputed.